If x 2 − 1 6 x = 1 2 , what is x − 2 x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Answer is given in title itself!
Let y = x . Then we have y 4 − 1 6 y y 4 − 1 6 y − 1 2 ( y 2 − 2 y − 2 ) ( y 2 + 2 y + 6 ) y 2 − 2 y − 2 y 2 − 2 y = 1 2 = 0 = 0 = 0 = 2 Only y 2 − 2 y − 2 has real roots We could solve for y , but note that x − 2 x = y 2 − 2 y = 2
Problem Loading...
Note Loading...
Set Loading...
x 2 − 1 6 x Adding 4 x + 4 x 2 + 4 x + 4 ⟹ ( x + 2 ) 2 ⟹ ( x + 2 ) 2 − ( 2 x + 4 ) 2 ( x + 2 + 2 x + 4 ) ( x + 2 − 2 x − 4 ) ⟹ x However, Setting x ⟹ ( x − 1 ) 2 The above equation has ⟹ ( x − 2 x ) = 1 2 (Given) to both sides, = 4 x + 1 6 x + 1 6 = ( 2 x + 4 ) 2 = 0 = 0 = 2 x + 2 or x = − 2 x − 6 = − 2 x − 6 = − 5 no real solution. = 2